Effect of acute respiratory infections in infancy on pulmonary function test at 3 years of age: a prospective birth cohort study - Kana Ram Jat; Sushil Kumar Kabra; Prawin Kumar; Aparna Mukherjee; Shivani Randev; Guruprasad R Medigeshi; Arti Kapil; Rakesh Lodha (BMJ Open Respiratory Research)
Introduction Acute respiratory infections (ARIs) in infancy may have a long-term impact on the developing respiratory system. We planned a prospective cohort study to determine the impact of ARI during infancy on the pulmonary function test indices at 3 years of age.Methods A cohort of normal, full-term newborns were followed up 6 monthly and during ARI episodes. Infant pulmonary function tests (IPFTs) were performed at baseline and each follow-up visit using tidal breathing flow-volume loop, rapid thoracoabdominal compression (RTC) and raised volume RTC manoeuvres. During each ARI episode, nasopharyngeal aspirates were tested for respiratory pathogens by real-time PCR.Results We screened 3421 neonates; 310 were enrolled; IPFT was performed in 225 (boys: 125 (55.6%)) at 3 years. During infancy, 470 ARI episodes were documented in 173 infants. At 3 years, children with history of any ARI episode during infancy had lower forced expiratory volume in 1 s (FEV1.0), forced expiratory volume in 0.75 s (FEV0.75), forced expiratory volume in 0.5 s (FEV0.5), forced expiratory flow between 25% and 75% of FVC (FEF25–75), and maximal expiratory flow at 25% of FVC (MEF25) as compared with those without any ARI episode during infancy. The ratio of tidal expiratory flow (TEF) at 25% or 50% of tidal expiratory volume to peak TEF (TEF50 or TEF25/peak TEF) at 3 years was significantly increased in children who had ARI in infancy.Conclusions ARI during infancy is associated with impaired pulmonary function indices such as increased resistance and decreased forced expiratory flow and volume at 3 years of age.